2015 Annual IEEE Systems Conference (SysCon) Proceedings 2015
DOI: 10.1109/syscon.2015.7116733
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing semantic relationships between multiformalism models for inconsistency management

Abstract: The involvement of multiple stakeholders in the design of complex engineered system presents many challenges. One of the challenge is that the overlapping stakeholder concerns leads to semantic relationships appearing between models. From an inconsistency management perspective, it is critical to investigate how these relationships appear and what are their types. Based on a decision-theoretic foundation, this paper investigates the types of semantic relationships between multiformalism models. We argue that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Hehenberger et al [8] is limited to identifying inconsistencies, but they did not support the method by techniques to resolve them. Qamar et al [7] presented a dependency modeling language to capture the dependencies between properties in multiple views of a system. Dependencies between these properties are interesting to identify inconsistencies between models but it is insufficient to manage consistency since it considers specific types of inconsistencies (i.e., related to properties).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hehenberger et al [8] is limited to identifying inconsistencies, but they did not support the method by techniques to resolve them. Qamar et al [7] presented a dependency modeling language to capture the dependencies between properties in multiple views of a system. Dependencies between these properties are interesting to identify inconsistencies between models but it is insufficient to manage consistency since it considers specific types of inconsistencies (i.e., related to properties).…”
Section: Discussionmentioning
confidence: 99%
“…Spanoudakis [6] presented a survey of the many techniques and methods used to support inconsistency management in various software models. Qamar et al [7] proposed a conceptual approach to explicitly capture dependencies across a set of models as an aid for consistency management. Hehenberger et al [8] suggested the use of domain-spanning ontologies for the purpose of identifying overlaps between mechatronic design models.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in the past have adopted model‐centric approaches to represent knowledge, 9,10 specifically in the context of requirements, and to evaluate inconsistencies in heterogenous models in the context of MBSE 11–13 . Past work has focused on developing domain‐specific languages for design synthesis with SysML metamodel as the basis 13 .…”
Section: Introductionmentioning
confidence: 99%